Populasi, Produksi, dan Skenario Pengembangan Ayam Hutan Merah Endemik Rejang Lebong - Sutriyono, Sutriyono; Santoso, Urip; Putranto, Heri Dwi; Suherman, Dadang; Warnoto, Warnoto (Buletin Peternakan Tropis, 2024)
The chicken endemic in Rejang Lebong Regency, Bengkulu Province, called burgo chicken, is the result of a cross between red jungle fowl and native chickens. The research aims to evaluate the production potential, population and population development scenarios of burgo chickens. The research was conducted in Rejang Lebong Regency, Bengkulu Province for 3 months. Fifteen breeders obtained using the snowball sampling method were used in this research. Data was obtained through interviews, filling out questionnaires, and observation; namely egg production, chick production, and population. Data is tabulated, discussed descriptively, and population development scenarios are prepared. The results of the research showed that the burgo population was 92 hens, 55 roosters, 17 hens, and 20 chicks. The productive hen was 13, producing 43.76 eggs/hen/year, a total of 744 eggs/13 hen/year, 386 (51.88%) were incubated by the hen, and 340 eggs (88.08%) hatched. In conclusion, egg production per individual is quite high, chick production is low, and population development is slow due to the low number of eggs laid, high chick mortality, being eaten by predators, sold and consumed by breeders. The scenario for increasing population and production is to increase the number of hens, the number of eggs laid, reduces mortality, protects chickens from predators, and improves rearing management.   Key words: Burgo Chicken, Production and Population, Development Scenarios   ABSTRAK Ayam endemik di Kabupaten Rejang Lebong, Provinsi Bengkulu yang disebut ayam burgo  merupakan hasil persilangan antara ayam hutan merah dengan ayam kampung. Penelitian bertujuan untuk mengevaluasi  potensi produksi, populasi dan skenario pengembangan populasi ayam burgo. Penelitian dilakukan  di Kabupaten Rejang Lebong, Provinsi Bengkulu selama 3 bulan. Lima belas peternak yang diperoleh dengan metode snowball sampling digunakan dalam penelitian ini. Data diperoleh melalui wawancara, mengisi kuisioner, dan observasi; yaitu produksi telur,  produksi anak ayam, dan populasi. Data ditabulasi, dibahas secara deskriptif, dan disusun skenario pengembangan  populasi. Hasil penelitian,  populasi burgo adalah 92 ekor ayam terdiri dari ayam jantan 55 ekor,  induk ayam 17 ekor, dan anak ayam 20 ekor. Induk ayam produktif berjumlah 13 ekor, menghasilkan  telur 43,76 butir telur/induk ayam/tahun, total 744 butir telur/13 induk ayam/tahun. Jumlah telur dieram induk ayam adalah   386  (51,88%) dan  340 butir telur (88,08%) menetas.  Kesimpulan, produksi telur per individu cukup tinggi, produksi anak ayam rendah, dan  perkembangan populasi lambat yang disebabkan oleh rendahnya jumlah telur dieram, tingginya kematian anak ayam, dimakan predator, dijual dan dikonsumsi oleh peternak. Skenario peningkatan populasi dan produksi adalah meningkatkan jumlah induk ayam, jumlah telur dieram,  menurunkan angka kematian, melindungi ayam dari predator, dan memperbaiki manajemen pemeliharaan.   Kata kunci: Ayam Burgo, Produksi dan Populasi, Skenario Pengembangan